2006
DOI: 10.1590/s1516-31802006000500007
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck reconstruction using infrahyoid myocutaneous flaps

Abstract: IHF is a safe and reliable procedure for reconstructing head and neck surgical defects. Due to its thinness and malleability, its use for oral cavity and oropharynx defects provides favorable cosmetic and functional outcomes. Complications, when present, are easy to manage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 6 publications
0
18
0
2
Order By: Relevance
“…Furthermore, the finding supported that the IMF might be suitable for small-and middle-size defects 3,4) .…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Furthermore, the finding supported that the IMF might be suitable for small-and middle-size defects 3,4) .…”
Section: Discussionmentioning
confidence: 59%
“…The harvest of an IMF was performed based on previous studies [2][3][4][5][6][7] . The IMF was elevated from caudal to cephalad.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7). Some put particular emphasis on the preservation of the cranial portion of the anterior jugular vein [12,13,21,22], which is perfectly feasible and reliable, nevertheless preservation of the external jugular system makes ipsilateral neck dissection technically more demanding.…”
Section: Technical Modificationsmentioning
confidence: 99%
“…Various types of loco-regional and free flaps are used for oropharyngeal reconstruction; but, at present, this issue remains the subject of debate since no 'ideal method' for all situations exists (11,14). The infrahyoid flap (IHF), introduced by Wang et al in 1986 (15), has been demonstrated to be a good alternative to for the reconstruction of small-or medium-sized defects in the oral cavity, oropharynx, hypopharynx and lower third of the face (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). In the present study, a prospective clinical study was performed on a series of consecutive patients with advanced OPSCC, with the aim of defining the principal characteristics and outcomes of oropharyngeal defect reconstruction with a simultaneously harvested IHF.…”
Section: Introductionmentioning
confidence: 99%